Moment of Truth: Hotel Operation in The New Normal Time Towards Customer Loyalty Mediated by Customer Satisfaction - Yustisia Pasfatima Mbulu; Daniel Widjaja; Sylvia Samuel (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2023)
The purpose of this study is to analyze the effect of Zero Moment of Truth on the satisfaction of prospective hotel guests, analyze the First Moment of Truth's influence on the satisfaction of prospective hotel guests, analyze the Second Moment of Truth that affects the satisfaction of hotel guests, analyze the Ultimate Moment of Truth that affect the satisfaction of hotel guests and analyze the effect of satisfaction on loyalty. This study uses a quantitative approach with SEM analysis methods and uses the Smart PLS 3.2.9 program. The sample was selected using a purposive sampling technique with 150 respondents, specifically for hotel guests in Jakarta who stay in the new normal period. The results of the study stated that the First Moment of Truth has a positive influence on the satisfaction of prospective hotel guests, the Ultimate Moment of Truth has a positive influence on the satisfaction of hotel guests, and the satisfaction of hotel guests has a positive influence on loyalty. Meanwhile, Zero moment of truth does not positively influence the satisfaction of prospective hotel guests, and the Second moment of truth does not positively influence hotel guest satisfaction.